Analysis of the Determinants of Zakat Crowdfunding Platform Usage - Lubis, Sri Nikmah Tullah; Harahap, Muhammad Ikhsan; Nasution, Juliana (Management of Zakat and Waqf Journal (MAZAWA), 2025)
This study aims to investigate the factors influencing the use of Zakat crowdfunding platforms for paying Zakat through digital applications, addressing the challenge of low public adoption of digital Zakat payment methods. A quantitative approach using Structural Equation Modeling (SEM) was employed. The sample consisted of 100 respondents drawn from the population of digital Zakat users in [sebutkan lokasi atau komunitas, misal: Indonesia]. The results indicate that convenience (X1), security (X2), and credibility (X4) have a positive and significant effect on platform usage, while transparency (X3) shows a positive but insignificant effect. Among these variables, security exhibits the strongest influence on usage, particularly through the indicator of data protection. These findings suggest that enhancing platform security could substantially increase user adoption of Zakat crowdfunding platforms